2013
DOI: 10.1007/s10029-013-1069-8
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of mesh-site infection in hernia repair surgery: a case series

Abstract: This series of case studies indicate that conservative management of abdominal wall-infected hernia mesh cases is likely to be successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Others have found similar results. 54 This finding again emphasizes the importance of decreased surface area for decreased bacterial attachment and rapid and increased tissue incorporation.…”
Section: The Modern Era and Lightweight Meshmentioning
confidence: 82%
“…Others have found similar results. 54 This finding again emphasizes the importance of decreased surface area for decreased bacterial attachment and rapid and increased tissue incorporation.…”
Section: The Modern Era and Lightweight Meshmentioning
confidence: 82%
“…Seven days following drainage removal, the patient presented with a subcutaneous effusion positive for Klebsiella pneumoniae. This required a percutaneous drainage within the fluid collection and infusion of 200 mg vancomycin in 10 mL saline solution through the drain twice a day for 7 days [8][9][10]. Since the problem did not resolve, we removed the mesh and used a medication with a single-use negative-pressure wound therapy system (PICO, Smith and Nephew, Hull, UK).…”
Section: Resultsmentioning
confidence: 99%
“…postoperative rates of 11%, 10%-17%, and as many as 40% of In the present study, our case presented reported overall infection 19% and 25% in preperitoneal space rates of surgical site the intraperitoneal abdominal abscesses were of the preperitoneal published in literatures on the extent of extensively studied. infection can increase taken for conservative wound care [25] or technique or percutaneous observed that surgical extent of hospital stay with drainage of of hospital stay and Incidence of surgical site infection is high in case of has its direct effect on the extent of hospital stay and time off from work and those with drainage of preperitoneal space showed more time of hospital…”
Section: Resultsmentioning
confidence: 99%